TEACHING CRAFT AS AN ART: TEACHER’S REPERTOIRE OF SKILLS AND STRATEGIES VIA PROFESSIONAL ENHANCEMENT - Damaiao, Creensanita D.; Obaob, Geronimo S. (European Scientific Journal, ESJ, 2015)
This research discloses one of the dimensions of the teachers’ quality of work life among secondary teachers. It was found out that professional growth and development through continuing education had a significant correlation with the amount of trainings that the teachers had. The more training the teachers had engaged with, the better they become as a professional teacher. It equipped them to be more productive and skillful. They felt the great importance of this dimension in their teaching career. Teachers became aware of the current trends and innovations through career progression. It also showed the greatest impact on the teachers quality of work life. Teachers positively embraced the significant contributions it could bring to the teaching profession and that secondary teachers could possess varied repertoire of skills and strategies in the teaching and learning process through professional growth and continuing education.